Reclassification Risk in the Small Group Health Insurance Market - Fleitas, Sebastian; Gowrisankaran, Gautam; Lo Sasso, Anthony (The Review of Economics and Statistics, 2025)
Abstract We evaluate health insurance reclassification risk in the Small Group Market before ACA community rating regulations. We use detailed claims and premiums data from a large insurance company, controlling non parametrically for selection. We find a pass-through of 11% from changes in health risk to changes in premiums, with a stronger equilibrium relationship between the two. The pricing patterns are consistent with the insurer offering “guaranteed renewability” contracts with one-sided pricing commitment. The observed pricing policy adds 55% of the consumer welfare gain from community rating relative to experience rating, with welfare gains limited because of switching across insurance companies.